Business model innovation: Integrative review, framework, and agenda for future innovation management research - Patrick Spieth; Pascal Breitenmoser; Tobias Röth (Journal of Product Innovation Management, 2023)
The business model innovation (BMI) concept has become a well-established phenomenon of current academic research. While Foss and Saebi's ( Journal of Management , 2017, 43, 200–227) seminal literature review on BMI revealed 349 articles on BMI published between 1972 and 2015, an additional number of 1727 articles on the topic have been published since 2016. In contrast to this overall interest in the BMI phenomenon, innovation-focused journals include only a limited number of publications on BMI. Further, besides the valuable insights and fruitful research directions of extant literature reviews, they tend also to overlook the linkages between traditional innovation management and the majority of BMI research. Given this underrepresentation of BMI research in the innovation management literature, we conduct an integrative literature review to bring the disconnected literature closer together and offer directions for future research. Our literature review applies the review strategy of blending and merging the literature across domains. First, we blend the knowledge base of the BMI domain by applying the Product Development and Management Association (PDMA) Body of Knowledge categories. Second, we merge the literature across domains by developing an integrative framework. As recent BMI literature increasingly converged to two lines of research, our framework differentiates between the relatedness of the BMI and BMI openness. Thereby, we offer new avenues for future research that can enrich the dialogue on BMI research in the innovation management community. These results demonstrate how the BMI domain covers aspects that fit, contribute to, and extend classical innovation-focused research, how both research domains can be merged to enrich each other, and how future research can foster the dialogue across disconnected domains.
Keywords: 650; blending and merging; business model innovation; integrative literature review; integrative theoretical framework